การพัฒนารูปแบบการเรียนการสอนอ่านภาษาอังกฤษโดยบูรณาการแนวคิด การอ่านแบบชี้แนะกับกลวิธีความสัมพันธ์ของคำถามและคำตอบเพื่อเสริมสร้างความสามารถในการอ่านเชิงวิเคราะห์ของนักเรียนมัธยมศึกษาตอนปลาย - อินทร์สุข พัชราวลัย; ชุษณะโชติ ฤดีรัตน์ (Journal of Education Studies, Chulalongkorn University, 2019)
The purposes of this study were to develop and study the effectiveness of an English reading instructional model integrating the guided reading approach and question-answer relationship strategy to enhance the analytical reading ability of upper secondary school students. The sample was drawn using purposive sampling totaling 32tenth-grade students of Talingchanwittaya School, Suphanburi. The instrument for collecting data was an analytical reading ability test. The data were analyzed by the Arithmetic Mean, Standard Deviation, and t-test. The findings revealed that an English reading instructional model integrating the guided reading approach and question-answer relationship consisted of 5 steps: activating, rehearsing, group reading, individual reading, and responding to text. The analytical reading ability of the sampled students was higher after the experiment at the .05 level of significance and the analytical reading ability of the sampled students in good, moderate and poor English ability level groups was higher after the experiment at the .05 level of significance.